Chondromesenchymal Hamartoma of the Anterior Cells of the Ethmoidal Labyrinth - Sergey Yakovlevich, Kosyakov; Ekaterina Vitalievna, Pchelenok; Olga Yurievna, Tarasova (ENT Updates, 2022)
Nasal chondromesenchymal hamartoma is a benign tumor of the sinonasal tract that arises in young and older children. Here, we report a rare clinical case of nasal chondromesenchymal hamartoma in a 15-year-old patient. After performing the necessary diagnostic tests, surgical treatment was recommended for the patient. In the course of surgery, a mass in the area of the anterior cells of the labyrinth was removed. According to the histological examination of the operative material, the mass had the structure of a chondromesenchymal hamartoma.